Lactulose to the Rescue: A Case of Toxic Hepatic Encephalopathy Caused by Portosystemic Shunting and Epistaxis in a Patient with Hereditary Hemorrhagic Telangiectasia - Ruchit N. Shah; Michael Makar; Nasir Akhtar; Erin Forster (Case Reports in Hepatology)
Hereditary hemorrhagic telangiectasia (HHT) is an uncommon autosomal dominant disorder characterized by telangiectasias and arteriovenous malformations. Multiple organ systems are involved including the skin, lungs, gastrointestinal tract, and brain. Hepatic encephalopathy is an extremely rare complication of HHT and early diagnosis and treatment can be life-saving. We present a rare case of hepatic encephalopathy caused by HHT-induced portosystemic shunting treated with lactulose.